Development of a parallel direct simulation code to investigate reactive flows - Thévenin, Dominique; Behrendt, Frank; Maas, Ulrich; Przywara, B.; Warnatz, Jürgen (Computers & fluids, 1996)
Solving the Navier-Stokes equations with detailed modeling of the transport and reaction terms remains at the present time a very difficult challenge. Direct simulations of two-dimensional reactive flows using accurate models for the chemical reactions generally require days of computing time on today's most powerful serial vector supercomputers. Up to now, realistic three-dimensional simulations remain practically impossible. Working with parallel computers seems to be at the present time the only possible solution to investigate more complicated problems at acceptable costs, however, lack of standards on parallel architectures constitutes a real obstacle. In this paper, we describe the structure of a parallel two-dimensional direct simulation code using detailed transport, thermodynamic and reaction models. Separating the modules controlling the parallel work from the flow solver, it is possible to get a high compatibility degree between parallel computers using distributed memory and message-passing communication. A dynamic load-balancing procedure is implemented in order to optimize the distribution of the load among the different nodes. Efficiencies obtained with this code on many different architectures are given. First examples of application conceding the interaction between vortices and a diffusion flame are shown in order to illustrate the possibilities of the solver.
Elektronische Reproduktion der Druck-Ausgabe 3. Mai 1999
Gesehen am 19.04.2023